Metal-free glycosylation with glycosyl fluorides in liquid SO2 - Gulbe, Krista; Lugiņina, Jevgeņija; Jansons, Edijs; Kinens, Artis; Turks, Māris (Beilstein Journal of Organic Chemistry, 2021)
Liquid SO2 is a polar solvent that dissolves both covalent and ionic compounds. Sulfur dioxide possesses also Lewis acid properties, including the ability to covalently bind Lewis basic fluoride ions in a relatively stable fluorosulfite anion (FSO2−). Herein we report the application of liquid SO2 as a promoting solvent for glycosylation with glycosyl fluorides without any external additive. By using various temperature regimes, the method is applied for both armed and disarmed glucose and mannose-derived glycosyl fluorides in moderate to excellent yields. A series of pivaloyl-protected O- and S-mannosides, as well as one example of a C-mannoside, are synthesized to demonstrate the scope of the glycosyl acceptors. The formation of the fluorosulfite species during the glycosylation with glycosyl fluorides in liquid SO2 is proved by 19F NMR spectroscopy. A sulfur dioxide-assisted glycosylation mechanism that proceeds via solvent separated ion pairs is proposed, whereas the observed α,β-selectivity is substrate-controlled and depends on the thermodynamic equilibrium.
Keywords: fluorosulfite; glycosyl fluoride; Lewis acid; liquid sulfur dioxide; metal-free glycosylation

Selective Glycosylations: Synthetic Methods and Catalysts - Bennett, C. S. (Wiley-VCH, 2017)

Glycoscience: Chemistry and Chemical Biology - Fraser-Reid, B. O.; Tatsuta, K.; Thiem, J.; Coté, G. L.; Flitsch, S.; Ito, Y.; Kondo, H.; Nishimura, S.-i.; Yu, B. (Springer, 2008)

Handbook of Chemical Glycosylation: Advances in Stereoselectivity and Therapeutic Relevance - Demchenko, A. V. (Wiley-VCH, 2008)

(untitled) - Nielsen, M. M.; Pedersen, C. M. (Chem. Rev., 2018)

(untitled) - Yokoyama, M. (Carbohydr. Res., 2000)

(untitled) - Mukaiyama, T.; Murai, Y.; Shoda, S.-i. (Chem. Lett., 1981)

Handbook of Chemical Glycosylation: Advances in Stereoselectivity and Therapeutic Relevance - Shoda, S.-I.; Kulkarni, S. S.; Gervay-Hague, J. (Glycoside Synthesis from Anomeric Halides, 2008)

(untitled) - Shimizu, M.; Togo, H.; Yokoyama, M. (Synthesis, 1998)

(untitled) - Williams, S. J.; Withers, S. G. (Carbohydr. Res., 2000)

(untitled) - Kaeothip, S.; Demchenko, A. V. (Carbohydr. Res., 2011)

(untitled) - Kulkarni, S. S.; Wang, C.-C.; Sabbavarapu, N. M.; Podilapu, A. R.; Liao, P.-H.; Hung, S.-C. (Chem. Rev., 2018)

(untitled) - Pearson, R. G. (J. Am. Chem. Soc., 1963)

(untitled) - Pearson, R. G.; Songstad, J. (J. Am. Chem. Soc., 1967)

(untitled) - Toshima, K. (Carbohydr. Res., 2000)

Glycoscience: Chemistry and Chemical Biology - Toshima, K. (Glycosyl Halides, 2008)

(untitled) - Mukaiyama, T.; Jona, H. (Proc. Jpn. Acad., Ser. B, 2002)

(untitled) - Mukaiyama, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Mukaiyama, T.; Maeshima, H.; Jona, H. (Chem. Lett., 2001)

(untitled) - Matsumoto, T.; Maeta, H.; Suzuki, K.; Tsuchihashi, l. G.-i. (Tetrahedron Lett., 1988)

(untitled) - Suzuki, K.; Maeta, H.; Matsumoto, T. (Tetrahedron Lett., 1989)

(untitled) - Matsumoto, T.; Katsuki, M.; Suzuki, K. (Tetrahedron Lett., 1989)

(untitled) - Kunz, H.; Sager, W. (Helv. Chim. Acta, 1985)

(untitled) - Jona, H.; Mandai, H.; Chavasiri, W.; Takeuchi, K.; Mukaiyama, T. (Bull. Chem. Soc. Jpn., 2002)

(untitled) - Manabe, S.; Ito, Y. (J. Org. Chem., 2013)

(untitled) - Ma, T.; Li, C.; Zhang, Z.-x.; Wang, Z.; Yu, L.; Xue, W. (Synlett, 2017)

(untitled) - Sim, J.; Kim, S.-H.; Hur, J.; Lim, C.; Kim, H. S.; Suh, Y.-G. (Asian J. Org. Chem., 2019)

(untitled) - Sati, G. C.; Martin, J. L.; Xu, Y.; Malakar, T.; Zimmerman, P. M.; Montgomery, J. (J. Am. Chem. Soc., 2020)

(untitled) - Zeng, J.; Vedachalam, S.; Xiang, S.; Liu, X.-W. (Org. Lett., 2011)

(untitled) - Okada, Y.; Asakura, N.; Bando, M.; Ashikaga, Y.; Yamada, H. (J. Am. Chem. Soc., 2012)

(untitled) - Heuckendorff, M.; Pedersen, C. M.; Bols, M. (J. Org. Chem., 2013)

(untitled) - Motoyama, A.; Arai, T.; Ikeuchi, K.; Aki, K.; Wakamori, S.; Yamada, H. (Synthesis, 2018)

(untitled) - Pelletier, G.; Zwicker, A.; Allen, C. L.; Schepartz, A.; Miller, S. J. (J. Am. Chem. Soc., 2016)

(untitled) - Wadzinski, T. J.; Steinauer, A.; Hie, L.; Pelletier, G.; Schepartz, A.; Miller, S. J. (Nat. Chem., 2018)

(untitled) - Yang, Y.; Zhang, X.; Yu, B. (Nat. Prod. Rep., 2015)

(untitled) - Pellissier, H. (Tetrahedron, 2005)

(untitled) - Yang, Y.; Yu, B. (Chem. Rev., 2017)

(untitled) - Cardona, A.; Boutureira, O.; Castillón, S.; Díaz, Y.; Matheu, M. I. (Green Chem., 2017)

Ullmann’s Encyclopedia of Industrial Chemistry - Müller, H. (Sulfur Dioxide, 2012)

The Chemistry of Nonaqueous Solvents - Burow, D. F. (Liquid Sulfur Dioxide, 1970)

(untitled) - Walden, P. (Ber. Dtsch. Chem. Ges., 1902)

(untitled) - Ross, J.; Percy, J. H.; Brandt, R. L.; Gebhart, A. I.; Mitchell, J. E.; Yolles, S. (Ind. Eng. Chem., Ind. Ed., 1942)

(untitled) - Tokura, N. (Synthesis, 1971)

(untitled) - Schmidt, D.; Leutbecher, H.; Conrad, J.; Klaiber, I.; Mika, S.; Greiner, G.; Beifuss, U. (Synlett, 2007)

(untitled) - Lugiņina, J.; Uzuleņa, J.; Posevins, D.; Turks, M. (Eur. J. Org. Chem., 2016)

(untitled) - Lugiņina, J.; Turks, M. (Synlett, 2017)

(untitled) - Olah, G. A.; Donovan, D. J. (J. Am. Chem. Soc., 1978)

(untitled) - Feigel, M.; Kessler, H.; Leibfritz, D.; Walter, A. (J. Am. Chem. Soc., 1979)

(untitled) - Mayr, H.; Gorath, G.; Bauer, B. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Olah, G. A. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Soares, B. G. (Prog. Polym. Sci., 1997)

(untitled) - Chénedé, A.; Fleming, I.; Salmon, R.; West, M. C. (J. Organomet. Chem., 2003)

(untitled) - Posevins, D.; Suta, K.; Turks, M. (Eur. J. Org. Chem., 2016)

(untitled) - Suta, K.; Turks, M. (ACS Omega, 2018)

(untitled) - Leškovskis, K.; Lugiņina, J.; Suta, K.; Turks, M. (Key Eng. Mater., 2019)

(untitled) - Leškovskis, K.; Gulbe, K.; Mishnev, A.; Turks, M. (Tetrahedron Lett., 2020)

(untitled) - Igarashi, K.; Honma, T.; Irisawa, J. (Carbohydr. Res., 1970)

(untitled) - Milanova, E.; Benoit, R. L. (Can. J. Chem., 1977)

(untitled) - Lee, K.-Y.; Kim, C.-S.; Kim, H.-G.; Cheong, M.-S.; Mukherjee, D. K.; Jung, K.-D. (Bull. Korean Chem. Soc., 2010)

(untitled) - Kumar, A.; McGrady, G. S.; Passmore, J.; Grein, F.; Decken, A. (Z. Anorg. Allg. Chem., 2012)

(untitled) - Maulitz, A. H.; Boese, R.; Kuhn, N. (J. Mol. Struct.: THEOCHEM, 1995)

(untitled) - Eisfeld, W.; Regitz, M. (J. Am. Chem. Soc., 1996)

(untitled) - Christensen, H. M.; Oscarson, S.; Jensen, H. H. (Carbohydr. Res., 2015)

(untitled) - Nielsen, M. M.; Qiao, Y.; Wang, Y.; Pedersen, C. M. (Eur. J. Org. Chem., 2020)

(untitled) - Jona, H.; Takeuchi, K.; Mukaiyama, T. (Chem. Lett., 2000)

(untitled) - Pinnick, H. W.; Bal, B. S.; Lajis, N. H. (Tetrahedron Lett., 1978)

(untitled) - Morita, T.; Okamoto, Y.; Sakurai, H. (Tetrahedron Lett., 1980)

Lewis Basicity and Affinity Scales: Data and Measurement - Laurence, C.; Gal, J.-F. (John Wiley & Sons, 2010)

(untitled) - Olah, G. A.; Prakash, G. K. S.; Rasul, G. (J. Am. Chem. Soc., 2008)

(untitled) - Dere, R. T.; Zhu, X. (Org. Lett., 2008)

(untitled) - Bosco, M.; Rat, S.; Dupré, N.; Hasenknopf, B.; Lacôte, E.; Malacria, M.; Rémy, P.; Kovensky, J.; Thorimbert, S.; Wadouachi, A. (ChemSusChem, 2010)

(untitled) - Araki, Y.; Watanabe, K.; Kuan, F.-H.; Itoh, K.; Kobayashi, N.; Ishido, Y. (Carbohydr. Res., 1984)

(untitled) - Jünnemann, J.; Lundt, I.; Thiem, J. (Liebigs Ann. Chem., 1991)

(untitled) - Schene, H.; Waldmann, H. (Synthesis, 1999)

(untitled) - Toshima, K.; Kasumi, K.-i.; Matsumura, S. (Synlett, 1999)

(untitled) - Hansen, T.; Elferink, H.; van Hengst, J. M. A.; Houthuijs, K. J.; Remmerswaal, W. A.; Kromm, A.; Berdern, G.; van der Vorm, S.; Rijs, A. M.; Overkleeft, H. S.; Filippov, D. V.; Rutjes, F. P. J. T.; et al. (Nat. Commun., 2020)

(untitled) - Lemieux, R. U.; Hendriks, K. B.; Stick, R. V.; James, K. (J. Am. Chem. Soc., 1975)

(untitled) - Zhu, S.-Z.; Huang, Q.-C.; Wu, K. (Inorg. Chem., 1994)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2013)